Analisis determinan permintaan rumah subsidi dan kaitannya dengan ketimpangan pendapatan di Kabupaten Muaro Jambi (Studi Kasus Kecamatan Kumpeh Ulu) - Risma Tri Handayani; Erni Achmad; Rahma Nurjanah (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to: 1) identify and examine the socioeconomic factors influencing the demand for subsidized housing in Kumpeh Ulu Subdistrict, Muaro Jambi Regency; 2) examine how low income in Kumpeh Ulu Subdistrict, relates to the need for government-subsidized housing. The analytical tool used was logistic regression analysis. The results show: 1) female respondents were dominant at 50.8%, with 85.2% being married, and the most common highest level of education among respondents was high school at 45.9%. The most dominant occupation among respondents was non-civil servants at 90.2%, and the dominant age group was 31–55 years old at 67.2%, with an average household size of 4 people and an average price of subsidized housing ranging from Rp155,000,000 to Rp164,000,000, while the average respondent income was Rp3,000,000. 2) Simultaneously, the variables of income and years of schooling have a significant effect on the demand for subsidized housing in Kumpeh Ulu Subdistrict, whereas occupation and housing price do not have a significant effect. The Gini Ratio calculation result is 0.157; the level of income inequality among the study respondents is classified as low, indicating that the distribution of respondents’ income is relatively even.